THE STRUCTURE AND DIRECTIONS OF PREPARING FUTURE TEACHERS FOR THE DEVELOPMENT OF NATIONAL AND GENERAL CULTURAL COMPETENCIES IN STUDENTS (Scientific journal of the Fergana State University, 2024)
This article examines the structure and directions of training future teachers for the development of national and general cultural competencies among students, highlights in detail its necessity and pedagogical relevance